If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -3 = 9 + 9t Reorder the terms: -3 + 3t = 9 + 9t Solving -3 + 3t = 9 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -3 + 3t + -9t = 9 + 9t + -9t Combine like terms: 3t + -9t = -6t -3 + -6t = 9 + 9t + -9t Combine like terms: 9t + -9t = 0 -3 + -6t = 9 + 0 -3 + -6t = 9 Add '3' to each side of the equation. -3 + 3 + -6t = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -6t = 9 + 3 -6t = 9 + 3 Combine like terms: 9 + 3 = 12 -6t = 12 Divide each side by '-6'. t = -2 Simplifying t = -2
| 5c+12=7c+11.84 | | 10x+x^2=84 | | -3x-30x-75=0 | | -10y^2-4(5y^2-8)+6y= | | -x^2-4x=-47 | | -5+8(x-3)=17x+2-9x | | -x^2-4x= | | 18=0.2x+5 | | -3(-7-6n)=-11+2(4+5n) | | 52+14m=318 | | -9+10=m-9 | | 10x-4=6x+2 | | 7x+10=-60-7x | | 7x+10=-60-7x | | 2m+14-5(m-1)=9m-(5m-4)-8m+9 | | (6+x)*(10+x)=144 | | m^2-14+49=0 | | 33n-195=234 | | mx^2+(2m+3)x+(m-1)=0 | | -9m+51-9(m-3)=3m-(4m-4)-2m+1 | | 7x+17=52 | | 8+2n=20 | | 7+3n=19 | | 2y-6=5x+8 | | 9(r+8)= | | 24=x-36 | | 3t+9t=-110 | | 2x+x-6=90 | | 8+2n=4(5n) | | 4(6a-9)= | | 6.6x-5+x-1.7= | | -3+x=6 |